2021
DOI: 10.2754/avb202190030277
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity of heavy metals in fallow deer in vitro

Abstract: Sertoli cells play a crucial role in male fertility through boosting and regulating the differentiation of spermatogonial stem cells into mature sperm during spermatogenesis. Female ovarian follicles are responsible for the production of mature ova and control of ovarian steroidogenesis. Disruption of these structures through exposure to environmental pollutants is critical for reproductive health. Here, we derived primary cell cultures of Sertoli cells and ovarian follicles from fallow deer (Dama dama). Cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The authors determined the lowest observed adverse effect concentration (LOAEC) for each metal and reported it to be 25 µM for CdCl2 and 100 µM for PbCl2 (59). Another study tested the adverse effects of CdCl2, MeHgCl2 and PbCl2 through a variety of equal molar concentrations (0, 15, 30, 60, 125, 250 µM) (67).…”
Section: Heavy Metals Caused a Limited Increase In Ros Productionmentioning
confidence: 99%
“…The authors determined the lowest observed adverse effect concentration (LOAEC) for each metal and reported it to be 25 µM for CdCl2 and 100 µM for PbCl2 (59). Another study tested the adverse effects of CdCl2, MeHgCl2 and PbCl2 through a variety of equal molar concentrations (0, 15, 30, 60, 125, 250 µM) (67).…”
Section: Heavy Metals Caused a Limited Increase In Ros Productionmentioning
confidence: 99%